The The Effect of UVC Irradiation on the Structure and Swelling Properties of Chitosan Membranes Exposed to Magnetic Fields - Sari, Ida Wisnu; Nita, Wolfharditia Oktaviana; Rupiasih, Ni Nyoman; Sumadiyasa, Made (BULETIN FISIKA, 2019)
Abstract –  Research on the effect of UVC radiation exposure on the structure and swelling properties of chitosan membranes exposed to magnetic fields has been carried out. The membrane used is the 2% chitosan membrane that has been exposed to a magnetic field of 1.5 mT in a parallel direction for 2 hours at the time of its formation (formation reaction). Furthermore, the dry membrane obtained was cut to a certain size and irradiated by using UVC radiation for 5, 10, 15 and 30 minutes, each of which was given the names M 1 , M 2 , M 3 and M 4 . A comparison is a 2% chitosan membrane with exposure to a magnetic field for 2 hours without exposure to UVC radiation, which is called the control membrane (M 0 ). Characterizations conducted include thickness, swelling (water absorption) and FTIR spectrophotometer. FTIR analysis shows that the OH, NH, CH, C = O, CN, CO and COC functional groups observed on the M 0 membrane as well as on the M 1 , M 2 , M 3 , and M 4 membranes, with the peaks shifted to smaller or larger wavenumbers. The percentage of transmittance of these functional groups increases with increasing irradiation time from 5 to 15 minutes and decreases in 30 minutes irradiation.